UV photocuring adhesive, preparation method and application
By using dimethyl amino isophthalate-tetracyanobenzene spherical eutectic initiator in UV light curing adhesive, the problem of poor curing effect caused by insufficient UV light is solved and the adhesive is improved cross-linking density and stability of agent.
Patent Information
- Application Number
- CN202411677564.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-22
- Publication Date
- 2024-12-20
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing UV light curing adhesives lack cross-linking and curing when irradiated with a lack of UV light source, resulting in poor curing effect.
Add dimethyl amino isophthalate-tetracyanobenzene spherical eutectic to the UV photocuring adhesive, and use its luminous properties to excite the light initiator to promote the cross-linking and curing of polyurethane acrylate and active diluted monomers Reaction and participate in the reaction under the action of photoinitiator through active functional groups to improve adhesive performance and stability.
In the case of insufficient UV light, spherical eutectics can excite the light initiator, promote the occurrence of cross-linking reactions, improve the curing effect and stability of the adhesive, and solve the problem of poor curing effect.
Smart Images

Figure CN119161848A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of adhesives and relates to a UV light-curing adhesive, a preparation method and an application thereof. Background Art
[0002] UV light-curing adhesive refers to an adhesive that uses ultraviolet light as an energy source to irradiate photoinitiators to produce active species such as free radicals or cations, thereby initiating rapid polymerization and cross-linking reactions of oligomers or monomers to achieve curing.
[0003] UV curing technology is characterized by high efficiency, wide adaptability, energy saving, environmental friendliness and economy. UV curing adhesives are widely used in smart phones, smart watches, tablet computers, TWS headphones and other electronic products to bond and fix components of electronic products due to their fast curing speed, controllable reaction, wide applicable substrates, high bonding strength, no volatile solvents and no pollution.
[0004] CN115386330B discloses a UV curing adhesive and a preparation method and application thereof. The UV curing adhesive comprises 40-80 parts by weight of polythiourethane acrylate oligomer, 1-40 parts by weight of active diluent, 0.5-5 parts by weight of photoinitiator, and 0-2 parts by weight of silane coupling agent. The UV curing adhesive has good flexibility, bonding strength, etc. However, its UV light curing technology requires irradiation by UV light source, and there is a problem of insufficient cross-linking and curing in the absence of UV light source irradiation.
[0005] In view of the above problems, the present application develops a new type of UV-curable adhesive to solve the problem of insufficient cross-linking and curing in the absence of UV light source irradiation. Summary of the invention
[0006] In view of the deficiencies in the prior art, the present invention aims to provide a UV light-curing adhesive, a preparation method and an application thereof; by innovatively adding 4-aminoisophthalic acid dimethyl ester-tetracyanobenzene spherical eutectic into the UV light-curing adhesive, firstly, the spherical eutectic has good luminescence performance, can excite the photoinitiator, promote the cross-linking and curing reaction of polyurethane acrylate and active diluent monomer, and is convenient for solving the problem of poor curing effect caused by insufficient ultraviolet light in practical applications; secondly, the 4-aminoisophthalic acid dimethyl ester-tetracyanobenzene spherical eutectic has good fluidity, is convenient for being evenly dispersed in the UV light-curing adhesive, and is convenient for better exciting the photoinitiator; then, the 4-aminoisophthalic acid dimethyl ester-tetracyanobenzene spherical eutectic has good fluidity, is convenient for being evenly dispersed in the UV light-curing adhesive, and is convenient for better exciting the photoinitiator; The surface of the ester-tetracyanobenzene spherical eutectic has active functional groups, which can also participate in the reaction under the action of a photoinitiator, thereby further increasing the adhesive performance and stability; by using polyurethane acrylate, active diluent monomer, 4-aminoisophthalic acid dimethyl ester-tetracyanobenzene spherical eutectic and a photoinitiator in combination, the photoinitiator can induce polymerization and crosslinking of the reactants under UV ultraviolet light irradiation; in the case of insufficient ultraviolet light, the 4-aminoisophthalic acid dimethyl ester-tetracyanobenzene spherical eutectic has good luminescence performance, which can excite the photoinitiator and promote the crosslinking and curing reaction of polyurethane acrylate and the active diluent monomer, and contains active functional groups, which can also participate in the reaction under the action of the initiator, thereby further promoting the crosslinking reaction.
[0007] To achieve this object, the present invention adopts the following technical solutions: One of the purposes of the present invention is to provide a UV light-curing adhesive, which comprises: 60-80 parts by weight of polyurethane acrylate (for example, 60 parts by weight, 65 parts by weight, 70 parts by weight, 75 parts by weight, 80 parts by weight), 10-40 parts by weight of reactive diluent monomer (for example, 10 parts by weight, 15 parts by weight, 20 parts by weight, 25 parts by weight, 30 parts by weight, 35 parts by weight, 40 parts by weight, etc.), 5-10 parts by weight of 4-aminoisophthalic acid dimethyl ester-tetracyanobenzene spherical crystals (for example, 5 parts by weight, 6 parts by weight, 7 parts by weight, 8 parts by weight, 9 parts by weight, 10 parts by weight, etc.), and 2-5 parts by weight of photoinitiator (for example, 2 parts by weight, 3 parts by weight, 4 parts by weight, 5 parts by weight, etc.); The preparation method of the 4-aminoisophthalic acid dimethyl ester-tetracyanobenzene spherical crystals comprises: (1) placing dimethyl 4-aminoisophthalate and tetracyanobenzene in a mixed solution of water and ethanol at 40-60° C. to form a mixture; (2) Chloroform is added to the mixture of step (1) to cool and crystallize, and then the mixture is grown to obtain spherical eutectic of 4-aminoisophthalic acid dimethyl ester-tetracyanobenzene.
[0008] In the present invention, 4-aminoisophthalic acid dimethyl ester-tetracyanobenzene spherical eutectic is innovatively added to the UV light-curing adhesive. Firstly, the spherical eutectic has good luminescence performance, can excite the photoinitiator, and promote the cross-linking and curing reaction of polyurethane acrylate and active diluent monomer, which is convenient for solving the problem of poor curing effect caused by insufficient ultraviolet light in practical applications; secondly, the 4-aminoisophthalic acid dimethyl ester-tetracyanobenzene spherical eutectic has good fluidity, which is convenient for uniform dispersion in the UV light-curing adhesive, and is convenient for better exciting the photoinitiator; and then, the surface of the 4-aminoisophthalic acid dimethyl ester-tetracyanobenzene spherical eutectic has active functional groups, which can also participate in the reaction under the action of the photoinitiator, and further increase the adhesive performance and stability.
[0009] In the present invention, during the preparation process of the spherical eutectic, a mixed solvent of ethanol and water is added to facilitate the growth of crystals, and under the wetting effect of chloroform, the two can be quickly agglomerated into a sphere to form a spherical eutectic; the spherical eutectic product formed by the method has uniform particle size distribution, good fluidity and is not easy to agglomerate.
[0010] In the present invention, the functions of the substances in the UV light-curing adhesive are as follows: Polyurethane acrylate: A radiation-curing material with excellent comprehensive properties, featuring good wear resistance, adhesion, flexibility, weather resistance, etc.
[0011] Reactive diluent monomers can reduce the viscosity of the system and can affect the curing kinetics, degree of polymerization and adhesive properties.
[0012] The spherical eutectic of 4-aminoisophthalic acid dimethyl ester-tetracyanobenzene has good luminescent properties and good fluidity, which makes it easy to be evenly dispersed in the adhesive. It also has active groups that can participate in the reaction under the action of the photoinitiator, further increasing the cross-linking density, thereby ensuring better adhesive properties and stability.
[0013] Photoinitiators absorb energy of a certain wavelength under the action of ultraviolet light or visible light to produce free radicals, cations, etc., thereby initiating the cross-linking and curing of polyurethane acrylates or monomers.
[0014] Preferably, the molar ratio of dimethyl 4-aminoisophthalate to tetracyanobenzene in step (1) is 1:1; Preferably, based on 1 g of the mixed solution, the sum of the amounts of dimethyl 4-aminoisophthalate and tetracyanobenzene added in step (1) is 0.3-0.5 g, such as 0.3 g, 0.35 g, 0.4 g, 0.45 g, 0.5 g, etc.
[0015] Preferably, in the mixed solution of step (1), the volume ratio of ethanol to water is 1:(10-15), such as 1:10, 1:12, 1:15, etc.
[0016] Preferably, the terminal temperature of the cooling crystallization in step (2) is 5-10°C (for example, 5°C, 8°C, 10°C, etc.), and the cooling rate of the cooling crystallization is 1-2°C / min (for example, 1°C / min, 1.2°C / min, 1.4°C / min, 1.6°C / min, 1.8°C / min, 2°C / min, etc.).
[0017] Preferably, the crystal growing time in step (2) is 10-30 min, for example, 10 min, 15 min, 20 min, 25 min, 30 min, etc.
[0018] Preferably, the polyurethane acrylate is made of the following raw materials in parts by weight: 60-85 parts by weight of polyester polyol (for example, 60 parts by weight, 65 parts by weight, 70 parts by weight, 75 parts by weight, 80 parts by weight, 85 parts by weight), 10-22 parts by weight of isocyanate (for example, 10 parts by weight, 15 parts by weight, 18 parts by weight, 20 parts by weight, 22 parts by weight, etc.), 5-18 parts by weight of hydroxyethyl acrylate (for example, 5 parts by weight, 8 parts by weight, 10 parts by weight, 12 parts by weight, 15 parts by weight, 18 parts by weight, etc.), 0.01-0.1 parts by weight of polymerization inhibitor (for example, 0.01 parts by weight, 0.03 parts by weight, 0.05 parts by weight, 0.08 parts by weight, 0.1 parts by weight, etc.) and 0.01-0.1 parts by weight of catalyst (for example, 0.01 parts by weight, 0.03 parts by weight, 0.05 parts by weight, 0.08 parts by weight, 0.1 parts by weight, etc.).
[0019] Preferably, the polyester polyol has a number average molecular weight of 2000-3000 (eg, 2000, 2200, 2500, 2800, 3000, etc.) and a functionality of 2.
[0020] Preferably, the polyester polyol is obtained by reacting sebacic acid with neopentyl glycol or 1,6-hexanediol; Preferably, the isocyanate is isophorone diisocyanate.
[0021] Preferably, the catalyst is an organotin catalyst and / or an amine catalyst; Preferably, the polymerization inhibitor is hydroquinone.
[0022] Preferably, the preparation method of the polyurethane acrylate comprises: At a temperature of 40-60°C (e.g., 40°C, 45°C, 50°C, 55°C, 60°C, etc.), isocyanate is added to the dehydrated polyester polyol, the temperature is raised to 80-85°C (e.g., 80°C, 81°C, 82°C, 83°C, 84°C, 85°C, etc.) and the reaction is carried out for 3-5 h (e.g., 3 h, 4 h, 5 h, etc.), and then the temperature is lowered to 40-60°C (e.g., 40°C, 45°C, 50°C, 55°C, 60°C, etc.), hydroxyethyl acrylate, an inhibitor and a catalyst are added, and the reaction is carried out for 3-5 h (e.g., 3 h, 4 h, 5 h, etc.) to obtain polyurethane acrylate.
[0023] Preferably, the active diluent monomer is tetrahydrofuran acrylate; Preferably, the photoinitiator is photoinitiator 184.
[0024] A second object of the present invention is to provide a method for preparing the UV light-curing adhesive as described in the first object, the preparation method comprising: 60-80 parts by weight of polyurethane acrylate, 10-40 parts by weight of active diluent monomer and 5-10 parts by weight of 4-aminoisophthalic acid dimethyl ester-tetracyanobenzene spherical eutectic are stirred and mixed, and then 2-5 parts by weight of photoinitiator are added for degassing and stirring and mixing, and then filtered and packaged with a 300 stainless steel mesh and centrifuged for degassing to obtain a UV light-curing adhesive.
[0025] Preferably, the stirring and mixing rate is 1200-1400 r / min (e.g., 1200 r / min, 1250 r / min, 1300 r / min, 1350 r / min, 1400 r / min, etc.), and the stirring and mixing time is 5-10 min (e.g., 5 min, 6 min, 7 min, 8 min, 9 min, 10 min, etc.).
[0026] The third object of the present invention is to provide an application of the UV light-curing adhesive as described in the first object in electronic products.
[0027] Compared with the prior art, the present invention has at least the following beneficial effects: In the present invention, 4-aminoisophthalic acid dimethyl ester-tetracyanobenzene spherical eutectic is innovatively added to the UV light-curing adhesive. Firstly, the spherical eutectic has good luminescence performance, can excite the photoinitiator, and promote the cross-linking and curing reaction of polyurethane acrylate and active diluent monomer, which is convenient for solving the problem of poor curing effect caused by insufficient ultraviolet light in practical applications; secondly, the 4-aminoisophthalic acid dimethyl ester-tetracyanobenzene spherical eutectic has good fluidity, which is convenient for uniform dispersion in the UV light-curing adhesive, and is convenient for better exciting the photoinitiator; and then, the surface of the 4-aminoisophthalic acid dimethyl ester-tetracyanobenzene spherical eutectic has active functional groups, which can also participate in the reaction under the action of the photoinitiator, and further increase the adhesive performance and stability.
[0028] In the present invention, polyurethane acrylate, reactive diluent monomer, 4-aminoisophthalic acid dimethyl ester-tetracyanobenzene spherical eutectic and photoinitiator are used in combination. Under UV ultraviolet light irradiation, the photoinitiator can induce polymerization and crosslinking of reactants. Under insufficient ultraviolet light, the 4-aminoisophthalic acid dimethyl ester-tetracyanobenzene spherical eutectic has good luminescence performance and can excite the photoinitiator, thereby promoting the crosslinking and curing reaction of polyurethane acrylate and the reactive diluent monomer. Moreover, the eutectic contains reactive functional groups and can also participate in the reaction under the action of the initiator, thereby further promoting the crosslinking reaction. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 is the XRD pattern of the spherical eutectic of 4-aminoisophthalic acid dimethyl ester-tetracyanobenzene prepared in Example 1 of the present invention; Figure 2 This is a scanning electron microscope image of the spherical eutectic of 4-aminoisophthalate-tetracyanobenzene prepared in Example 1 of the present invention. DETAILED DESCRIPTION
[0030] The technical solution of the present invention is described in detail below in conjunction with specific embodiments and their accompanying drawings. The embodiments recorded herein are specific embodiments of the present invention, which are used to illustrate the concept of the present invention; these descriptions are explanatory and exemplary and should not be construed as limitations on the embodiments of the present invention and the scope of protection of the present invention. In addition to the embodiments recorded herein, those skilled in the art can also adopt other obvious technical solutions based on the contents disclosed in the claims of this application and its specification, including technical solutions that adopt any obvious replacements and modifications to the embodiments recorded herein.
[0031] The brands, manufacturers and other information of the main chemical reagents used in the embodiments of the present invention and the comparative examples are as follows: 4-aminoisophthalic acid dimethyl ester, MacLean Reagent Network; tetracyanobenzene, Shijiazhuang Ahan Chemical Technology Co., Ltd.; ethanol, MacLean Reagent Network; chloroform, sebacic acid, neopentyl glycol, isophorone diisocyanate, dibutyltin dilaurate, hydroquinone, photoinitiator 184 and tetrahydrofuran acrylate, all purchased from Merck Life Sciences Co., Ltd.
[0032] Preparation Example 1 This preparation example provides a method for preparing polyurethane acrylate, comprising: Weigh polyester polyol by weight, dehydrate it at 110°C and a vacuum degree of -0.08 to -0.1 MPa for 1 hour, cool it to 50°C, add isocyanate, raise the temperature to 80-85°C and react for 3 hours, measure the NCO content to reach the set value, cool it to 60°C, add hydroxyethyl acrylate, inhibitor and catalyst, react at 60-65°C for 3 hours, and after the NCO content reaches the set value, the reaction is qualified and collected for use.
[0033] Preparation Example 2 This preparation example provides a method for preparing spherical eutectic of 4-aminoisophthalic acid dimethyl ester-tetracyanobenzene, comprising: (1) at a temperature of 50° C., placing dimethyl 4-aminoisophthalate and tetracyanobenzene in a molar ratio of 1:1 in a mixed solution of ethanol and water in a volume ratio of 1:10 to form a mixture; the mass ratio of the sum of dimethyl 4-aminoisophthalate and tetracyanobenzene to the mixed solution is 0.4:1; (2) Add chloroform (half the volume of the mixed solution) to the mixture, cool it to 10°C at a cooling rate of 1°C / min for crystallization, and keep it for 20 min. Filter and wash, and dry it at 50°C for 12 h to obtain spherical eutectics.
[0034] Figure 1 To obtain the XRD pattern of spherical eutectic, Figure 1 It can be seen that it has characteristic peaks at 10.8°, 12.7°, 14.9°, 15.3°, 16.9°, 17.3°, 18.2°, 18.6°, 19.7°, 20.7°, 21.2°, 21.4°, 22.3°, 23.1°, 23.6°, 24.1°, 25.6°, 26.0°, 26.3°, 26.5°, 27.5°, 28.1°, 28.6°, 29.0°, 29.3°, and 30.3°.
[0035] Figure 2 To obtain the scanning electron microscope image of the spherical eutectic, it can be found that it is a spherical crystal.
[0036] The spherical eutectic was tested and found to have an average fluorescence lifetime of 8.50 ns and a quantum yield of 4.87%, indicating good fluorescence properties.
[0037] Example 1
[0038] This embodiment provides a UV light-curing adhesive, the raw material composition of which is as follows: 70 parts by weight of polyurethane acrylate, 20 parts by weight of active diluent monomer, 8 parts by weight of 4-aminoisophthalic acid dimethyl ester-tetracyanobenzene spherical eutectic and 2 parts by weight of photoinitiator; polyurethane acrylate and 4-aminoisophthalic acid dimethyl ester-tetracyanobenzene spherical eutectic are prepared by Preparation Example 1 and Preparation Example 2; the active diluent monomer is tetrahydrofuran acrylate; the photoinitiator is photoinitiator 184.
[0039] The preparation method comprises: Polyurethane acrylate, reactive diluent monomer and 4-aminoisophthalic acid dimethyl ester-tetracyanobenzene spherical eutectic were stirred and mixed at a stirring rate of 1300 r / min for 8 min, and then a photoinitiator was added and stirred and mixed for degassing for 10 min. The mixture was then filtered and packaged with a 300 stainless steel mesh and centrifuged for degassing to obtain a UV light-curing adhesive.
[0040] Example 2
[0041] This embodiment provides a UV light-curing adhesive, the raw material composition of which is as follows: 80 parts by weight of polyurethane acrylate, 40 parts by weight of active diluent monomer, 10 parts by weight of 4-aminoisophthalic acid dimethyl ester-tetracyanobenzene spherical eutectic and 5 parts by weight of photoinitiator; polyurethane acrylate and 4-aminoisophthalic acid dimethyl ester-tetracyanobenzene spherical eutectic are prepared by Preparation Example 1 and Preparation Example 2; the active diluent monomer is tetrahydrofuran acrylate; the photoinitiator is photoinitiator 184.
[0042] The preparation method comprises: Polyurethane acrylate, reactive diluent monomer and 4-aminoisophthalic acid dimethyl ester-tetracyanobenzene spherical eutectic were stirred and mixed at a stirring rate of 1400r / min for 5 min, and then a photoinitiator was added and stirred and mixed for degassing for 10 min. The mixture was filtered and packaged with a 300 stainless steel mesh and centrifuged for degassing to obtain a UV light-curing adhesive.
[0043] Example 3
[0044] This embodiment provides a UV light-curing adhesive, the raw material composition of which is as follows: 60 parts by weight of polyurethane acrylate, 10 parts by weight of active diluent monomer, 5 parts by weight of 4-aminoisophthalic acid dimethyl ester-tetracyanobenzene spherical eutectic and 2 parts by weight of photoinitiator; polyurethane acrylate and 4-aminoisophthalic acid dimethyl ester-tetracyanobenzene spherical eutectic are prepared by Preparation Example 1 and Preparation Example 2; the active diluent monomer is tetrahydrofuran acrylate; the photoinitiator is photoinitiator 184.
[0045] The preparation method comprises: Polyurethane acrylate, reactive diluent monomer and 4-aminoisophthalic acid dimethyl ester-tetracyanobenzene spherical eutectic were stirred and mixed at a stirring rate of 1200r / min for 10 min, and then a photoinitiator was added and stirred and mixed for degassing for 5 min. The mixture was filtered and packaged with a 300 stainless steel mesh and centrifuged for degassing to obtain a UV light-curing adhesive.
[0046] Comparative Example 1 The difference from Example 1 is that the polyurethane acrylate is replaced by conventional polyurethane acrylate (U-CURE9100).
[0047] Comparative Example 2 The difference from Example 1 is that the spherical eutectic of 4-aminoisophthalic acid dimethyl ester-tetracyanobenzene is not included.
[0048] Comparative Example 3 The difference from Example 1 is that the 4-aminoisophthalic acid dimethyl ester-tetracyanobenzene cocrystal is a conventional rod-shaped crystal habit.
[0049] The adhesives prepared in Examples 1 to 3 and Comparative Examples 1 to 3 were subjected to the following performance tests: (1) Light curing performance test: The adhesives prepared in Examples 1 to 3 and Comparative Examples 1 to 3 were subjected to full UV curing tests using an LED ultraviolet lamp with a wavelength of 245 nm. 2 Under the condition of light, the curing was carried out at a distance of 2 cm for 10 seconds. As a comparative test, UV+ self-luminous curing was carried out: first, the surface of the adherend coated with Examples 1 to 3 and Comparative Examples 1 to 3 was covered, and the covering area was 3 / 4 of the coating area. Then, an LED ultraviolet lamp with a wavelength of 245 nm was used at an intensity of 1500 mj / cm 2 Under the light condition, the curing was carried out at a distance of 2cm. After 5s of irradiation, the surface covering was removed and irradiation was continued for 5S to obtain the comparative test piece. The tensile strength and elongation at break were tested according to GB / T 7124-2008 "Determination of tensile shear strength of adhesives". The results are shown in Table 1: Table 1 Test results of tensile strength and elongation at break of Example 1-Example 3 and Comparative Example 1-Comparative Example 3
[0050] By comparing Example 1 with Comparative Example 1, it can be seen that when the oligomer is an acrylate oligomer, the tensile strength and elongation of the adhesive are greatly reduced; by comparing Example 1 with Comparative Example 2, it can be seen that when spherical crystals are not included, the UV+ self-luminous curing effect is poor, and the tensile strength and elongation are greatly reduced; by comparing Example 1 with Comparative Example 3, it can be seen that when the eutectic adopts conventional rod-shaped crystals, it will affect the cross-linking situation, thereby affecting the tensile strength and elongation.
[0051] (2) Viscosity test: GB / T2794-2022 "Determination of viscosity of adhesives", test results are shown in Table 2: Table 2 Viscosity test results of Example 1-Example 3 and Comparative Example 1-Comparative Example 3
[0052] By comparing Example 1 with Comparative Example 1, it can be seen that the adhesive properties of the adhesive can be increased by treating the acrylate oligomer; by comparing Example 1 with Comparative Example 2, it can be seen that when the spherical eutectic is not included, the viscosity will decrease because the spherical eutectic participates in the reaction under the action of the initiator to further increase the crosslinking; by comparing Example 1 with Comparative Example 3, it can be seen that if the eutectic is a conventional rod-shaped crystal, the fluidity and dispersibility will deteriorate, thereby resulting in poor crosslinking performance.
[0053] (3) Adhesive performance test: GB / T7124-2008 "Determination of tensile shear strength of adhesives"; the adhesives prepared in Examples 1-3 and Comparative Examples 1-3 were coated between the polycarbonate substrate (PC) and the block polyetheramide resin (PEBAX substrate) (coating area 0.5*0.5=0.25cm 2 ), and irradiated and cured for 5 s. The test results are shown in Table 3: Table 3 Adhesion performance test results of Example 1-Example 3 and Comparative Example 1-Comparative Example 3
[0054] By comparing Example 1 with Comparative Example 1, it can be seen that when the oligomer is an acrylate oligomer, the tensile strength of the obtained adhesive is greatly reduced; by comparing Example 1 with Comparative Example 3, it can be seen that when the eutectic is a conventional rod-shaped crystal, it will affect the crosslinking situation and thus affect the tensile strength.
[0055] The applicant declares that the above is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention shall fall within the protection scope and disclosure scope of the present invention.
Claims
1. A UV light-curing adhesive, characterized in that: The UV light-curing adhesive comprises: 60-80 parts by weight of polyurethane acrylate, 10-40 parts by weight of reactive diluent monomer, 5-10 parts by weight of 4-aminoisophthalic acid dimethyl ester-tetracyanobenzene spherical eutectic and 2-5 parts by weight of photoinitiator; The preparation method of the 4-aminoisophthalic acid dimethyl ester-tetracyanobenzene spherical eutectic comprises: (1) placing dimethyl 4-aminoisophthalate and tetracyanobenzene in a mixed solution of water and ethanol at 40-60° C. to form a mixture; (2) Chloroform is added to the mixture of step (1) to cool and crystallize, and then the mixture is grown to obtain spherical eutectic of 4-aminoisophthalic acid dimethyl ester-tetracyanobenzene.
2. The UV light curing adhesive according to claim 1, characterized in that: The molar ratio of dimethyl 4-aminoisophthalate to tetracyanobenzene in step (1) is 1:1; Based on the addition amount of the mixed solution as 1 g, the sum of the addition amounts of dimethyl 4-aminoisophthalate and tetracyanobenzene in step (1) is 0.3-0.5 g; In the mixed solution of step (1), the volume ratio of ethanol to water is 1:(10-15); Based on the volume of the mixed solution being 1 mL, the volume of chloroform added in step (2) is 0.5-0.8 mL; The terminal temperature of the cooling crystallization in step (2) is 5-10°C, and the cooling rate of the cooling crystallization is 1-2°C / min; The crystal growing time in step (2) is 10-30 min.
3. The UV light curing adhesive according to claim 1, characterized in that: The polyurethane acrylate is prepared from the following raw materials in parts by weight: 60-85 parts by weight of polyester polyol, 10-22 parts by weight of isocyanate, 5-18 parts by weight of hydroxyethyl acrylate, 0.01-0.1 parts by weight of polymerization inhibitor and 0.01-0.1 parts by weight of catalyst.
4. The UV light curing adhesive according to claim 3, characterized in that: The polyester polyol has a number average molecular weight of 2000-3000 and a functionality of 2; The polyester polyol is obtained by reacting sebacic acid with neopentyl glycol or 1,6-hexanediol; The isocyanate is isophorone diisocyanate.
5. The UV light curing adhesive according to claim 3, characterized in that: The catalyst is an organotin catalyst and / or an amine catalyst; The polymerization inhibitor is hydroquinone.
6. The UV light curing adhesive according to claim 3, characterized in that: The preparation method of the polyurethane acrylate comprises: At a temperature of 40-60°C, add isocyanate to the dehydrated polyester polyol, raise the temperature to 80-85°C and react for 3-5 hours, then cool to 40-60°C, add hydroxyethyl acrylate, inhibitor and catalyst, and react for 3-5 hours to obtain polyurethane acrylate.
7. The UV light curing adhesive according to claim 1, characterized in that: The active diluent monomer is tetrahydrofuran acrylate; The photoinitiator is photoinitiator 184.
8. The method for preparing a UV light-curing adhesive according to any one of claims 1 to 7, characterized in that: The preparation method comprises: 60-80 parts by weight of polyurethane acrylate, 10-40 parts by weight of active diluent monomer and 5-10 parts by weight of 4-aminoisophthalic acid dimethyl ester-tetracyanobenzene spherical eutectic are stirred and mixed, and then 2-5 parts by weight of photoinitiator are added for degassing and stirring and mixing, and then filtered and packaged with a 300 stainless steel mesh and centrifuged for degassing to obtain a UV light-curing adhesive.
9. The method for preparing a UV light-curing adhesive according to claim 8, characterized in that: The stirring and mixing speed is 1200-1400 r / min, and the stirring and mixing time is 5-10 min.
10. Use of the UV light-curing adhesive according to any one of claims 1 to 7 in electronic products.
Citation Information
Patent Citations
Preparation method of ethyl vanillin spherical crystal
CN115043716A
4-amino dimethyl isophthalate-tetracyanobenzene eutectic as well as preparation method and application of 4-amino dimethyl isophthalate-tetracyanobenzene eutectic
CN118026869A
